Antispasmodic, cardioprotective and blood-pressure lowering properties of Gomphrena perennis L. and its mechanisms of action - Bonilla Bonilla, Adriana Milena (2023)
Background: Gomphrena perennis L. is a native plant of South America whose pharmacological properties have not been studied yet. Aim: To evaluate the cardiovascular and intestinal pharmacological effects of Gomphrena perennis L. leaves tincture (GphT) and the mechanisms involved. Experimental procedure: The chromatographic profile of GphT was done. Its ex vivo effects were evaluated by contractile concentration-response curves (CRCs) obtained from the agonist carbachol or calcium found in isolated rat small intestine, as well as in the relaxant CRCs. Cardiac effects were evaluated on isolated rat hearts exposed to ischemia/reperfusion (I/R). Experiments in vivo were performed to evaluate the diuretic activity in conscious rats and the hypotensive effect in anaesthetised rats. Results: Fifteen flavonoids were identified in GphT by HPLC-UV, including diosmin. GphT induced a noncompetitive inhibition in both carbachol and calcium CRCs on rat small intestine. The first was not affected by indomethacin. Moreover, GphT, unlike diosmin, relaxed the contracture produced by a high-potassium solution in a dose-dependently way. Neither propranolol nor L-NAME changed it. GphT did not show diuretic activity but induced hypotension insensitive to L-NAME. While GphT perfusion of isolated hearts increased injury consequent to I/R, oral administration was cardioprotective and reversed by L-NAME. However, diosmin did not improve the post-ischemic recovery. Conclusions: This study supports the use of Gomphrena perennis L. tincture as an antispasmodic and hypotensive agent. Moreover, it has been demonstrated to be preventive of post-ischemic cardiac dysfunction. However, diosmin would not be responsible for these effects.